THE ROLE OF PARTICIPATIVE LEADERSHIP IN IMPROVING EMPLOYEE PERFORMANCE IN EDUCATIONAL INSTITUTIONS: SYSTEMATIC LITERATURE REVIEW - Heni Apriliah, Nugra; Rindaningsih, Ida (Journal of Learning on History and Social Sciences, 2025)
Objective: This study aims to explore the role and impact of participative leadership on employee performance in educational institutions, focusing on decision-making and employee engagement. Despite existing research, gaps remain in understanding how participative leadership influences performance in the education sector. Method: The study employs a Systematic Literature Review (SLR) approach. Research questions were formulated to guide the review process. Relevant literature was collected from databases such as Scopus, Google Scholar, and PubMed. The collected studies were then analyzed to identify trends, patterns, and relationships between participative leadership and employee performance. Results: Findings indicate that participative leadership enhances employee performance by fostering a collaborative environment and increasing employee involvement in decision-making. This leadership style aligns with intrinsic motivation theory, highlighting that employee feel more responsible and productive when valued and empowered. However, the effectiveness of participative leadership varies depending on organizational culture and institutional structure, necessitating further context-specific studies. Novelty: This research contributes to participative leadership theory by emphasizing its significance in the education sector. It also highlights the moderating role of organizational factors and expands on intrinsic motivation theory. Practical implications include adopting democratic leadership strategies in educational institutions to enhance employee and organizational outcomes.